HOW TO IMPROVE LISTENING SKILLS OF BOTH ESL AND EFL STUDENTS - Mukhtorova, Mokhlaroyim; Ilxomov, Xojiakbar (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article examines a range of effective methods to improve the listening skills of ESL (English as a Second Language) and EFL (English as a Foreign Language) students. Listening is a fundamental aspect of language acquisition and proficiency, yet many learners find it challenging due to factors such as limited exposure to the target language, variations in accents, and rapid speech rates. This study highlights simple, practical strategies that can be seamlessly integrated into daily routines to enhance listening abilities. Key methods include consistent practice with diverse and engaging audio materials, the strategic use of digital technologies, and the implementation of interactive and passive listening activities. Additionally, this article explores the benefits of modern digital tools, such as language learning apps, podcasts, and vodcasts, which provide flexible and accessible platforms for continuous learning. By leveraging these tools, students can create a personalized and immersive listening environment that promotes active engagement and gradual improvement. The anticipated outcomes of this study include improved listening comprehension, increased vocabulary, better pronunciation, and heightened confidence in real-world communication scenarios. The findings aim to provide educators and learners with actionable insights and practical approaches to overcome common listening challenges in language learning.